The Survival Status of Golden and Steppe Eagles in a Capturing Area in China - Roller MaMing (Пернатые хищники и их охрана)
Our recent investigation in China encompasses the species and number studies of eagles in captivity, study of methods and tools used to capture raptors in the field, investigation into whether there is trade (and at which level), estimation of damage to wild populations and their resources, assessment of the current situation in the field, negative factors, conflicts between laws and traditional culture (such as the Intangible Cultural Heritage), and how to solve and effectively manage them.